Transgression and the Inexistent : a Philosophical Vocabulary - Belhaj Kacem, Mehdi, 1973- (Suspensions: Contemporary Middle Eastern and Islamicate Thought., 2014)
A contemporary philosopher of Tunisian origin, Mehdi Belhaj Kacem is here published in English for the first time. His new book, Transgression and the Inexistent: A Philosophical Vocabulary, is a comprehensive foray into Kacem''s elaborate philosophical system in twenty-seven discreet chapters, each dedicated to a single concept. In each chapter, he explicates a critical re-thinking of ordinary lived experiences - such as desire, irony, play - or traditional philosophical ideas such as catharsis, mimesis, techne in light of ''the spirit of nihilism'' that marks the contemporary human condi.